2000
DOI: 10.1001/jama.283.1.81
|View full text |Cite
|
Sign up to set email alerts
|

HPV DNA Testing of Self-collected Vaginal Samples Compared With Cytologic Screening to Detect Cervical Cancer

Abstract: These results indicate that HPV testing of self-collected vaginal swabs is less specific than but as sensitive as Papanicolaou smears for detecting high-grade cervical disease in women aged 35 years and older, and HPV testing offers an important new way to increase screening in settings where cytology is not readily performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
182
4
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(211 citation statements)
references
References 21 publications
(16 reference statements)
10
182
4
8
Order By: Relevance
“…Several studies have recently reported the possible use of SC vaginal samples for HPV DNA testing [17,18,19]. Dzuba et al [22] indicated that inherently private self-sampling for the HPV test was more acceptable in younger, wealthier and more educated women than the conventional Pap test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have recently reported the possible use of SC vaginal samples for HPV DNA testing [17,18,19]. Dzuba et al [22] indicated that inherently private self-sampling for the HPV test was more acceptable in younger, wealthier and more educated women than the conventional Pap test.…”
Section: Discussionmentioning
confidence: 99%
“…Dzuba et al [22] indicated that inherently private self-sampling for the HPV test was more acceptable in younger, wealthier and more educated women than the conventional Pap test. Although some studies reported that the sensitivity for detection of high-grade CIN in cytological specimens obtained from SC vaginal material was lower than that of conventional cytology, studies have shown that SC cervicovaginal specimens are highly representative of the high-risk HPV DNA status of the cervix [18,19,36,37,38]. A previous study using swabs as the SC device and a more sensitive PCR-based DNA detection method of high-risk HPV testing found SC cervicovaginal samples to be as reliable as physician-taken samples [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, many HIV-infected patients are not screened for anal cancer although they are at-risk individuals [2,5]. In the setting of cervical cancer screening, self-sampling techniques for the purpose of cervical cytology and HPV testing have been proposed as an appropriate and effective alternative to sampling performed by clinicians [14]. To date, only 3 studies have assessed anal self-sampling in HIV-positive and -negative MSM and in HIV-negative women [15,16,17], and 1 study has assessed feasibility, acceptability, and accuracy of anal self-sampling [18].…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies were similar. The sampling devices demonstrated a comparable sensitivity and a lower specificity when they were compared to conventional cytology, and these results were mainly due to the prevalence of nonpersistent HPV infections in young women [7,8,9]. …”
Section: Introductionmentioning
confidence: 99%